2018
DOI: 10.1017/thg.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Intrapair Birth-Weight Differences With Internalizing and Externalizing Behavior Problems

Abstract: Problem behaviors are of increasing public health concern. Twin studies have revealed substantial genetic and environmental influences on children's behavior, and examining birth-weight difference could allow the identification of the specific contribution of multiple non-shared prenatal environmental factors. The Twins and Multiple Births Association Heritability Study, a UK, volunteer-based study, recruited mothers of twins aged 18 months to 5 years; 960 twins (480 pairs) were included in the analysis. Twins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…For a categorical outcome, two large population-based sibling studies (Class et al, 2014;Pettersson et al, 2019) and a small twin study (N = 38) (Lehn et al, 2007) showed associations including a reported HR of 2.44 (95% CI, 1.99-2.97), an OR of 2.36 (95% CI, 2.27-2.43) and t (18) = −1.99, p (one-tailed) = .031, while a study with higher risk of bias reported no association (N = 1,464) (Chatterji et al, 2014). The same pattern was seen for a dimensional outcome, with two large population-based sibling studies (Jackson & Beaver, 2015;Lim et al, 2018) and two twin studies (N = 8,594) (Groen-Blokhuis et al, 2011;Hultman et al, 2007;Pettersson et al, 2015;Tore et al, 2018) reporting associations, while studies with higher risk of bias reported no associations or mixed results (N = 2,581) (Asbury et al, 2006;Mascheretti et al, 2017). Mixed results were seen for smoking (k = 11 studies) and alcohol use (k = 3) during pregnancy, parental age (k = 6) and maternal depression (k = 2).…”
Section: Prenatal Exposurementioning
confidence: 72%
“…For a categorical outcome, two large population-based sibling studies (Class et al, 2014;Pettersson et al, 2019) and a small twin study (N = 38) (Lehn et al, 2007) showed associations including a reported HR of 2.44 (95% CI, 1.99-2.97), an OR of 2.36 (95% CI, 2.27-2.43) and t (18) = −1.99, p (one-tailed) = .031, while a study with higher risk of bias reported no association (N = 1,464) (Chatterji et al, 2014). The same pattern was seen for a dimensional outcome, with two large population-based sibling studies (Jackson & Beaver, 2015;Lim et al, 2018) and two twin studies (N = 8,594) (Groen-Blokhuis et al, 2011;Hultman et al, 2007;Pettersson et al, 2015;Tore et al, 2018) reporting associations, while studies with higher risk of bias reported no associations or mixed results (N = 2,581) (Asbury et al, 2006;Mascheretti et al, 2017). Mixed results were seen for smoking (k = 11 studies) and alcohol use (k = 3) during pregnancy, parental age (k = 6) and maternal depression (k = 2).…”
Section: Prenatal Exposurementioning
confidence: 72%
“…In the literature, low birth weight has been related to adverse outcomes, such as poorer health status39 and the presence of mild neurological deficits,40 which may impair ability to attend school even in the absence of cognitive limitations. Moreover, behavioural factors might also play a role in the association between birth weight and educational attainment; previous twin studies have suggested a causal association of lower birth weight with child problem behaviour41 and more specifically with internalising problems and emotional reactiveness,42 which are strongly associated with poor educational attainment. Regarding other explanations than the direct influence of prenatal environmental factors, it is possible that differential parental interaction in postnatal life has a role: a greater parental care to the heavier twin may lead to better education, but there is no reason to think that this would be specific for MZ twins.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies of MZ twin pairs have shown that the lower BW twin has lower intelligence quotient scores, relative to the higher BW twin (Edmonds et al, 2010; Newcombe, Milne, Caspi, Poulton, & Moffitt, 2007). Other studies have found that greater BW discordance was associated with greater within‐pair differences in child problematic behavior (Lim et al, 2018; Tore et al, 2018; van Os et al, 2001). We and others have previously found in MZ twin pairs that overall brain volume and cortical surface area were positively associated with BW discordance in frontal and temporal brain regions in adolescents and adults (Casey et al, 2017; Levesque et al, 2015; Raznahan, Greenstein, Lee, Clasen, & Giedd, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…Interestingly, studies of MZ twin pairs have shown that the lower BW twin has lower intelligence quotient scores, relative to the higher BW twin (Edmonds et al, 2010;Newcombe, Milne, Caspi, Poulton, & Moffitt, 2007). Other studies have found that greater BW discordance was associated with greater within-pair differences in child problematic behavior (Lim et al, 2018;Tore et al, 2018;van Os et al, 2001).…”
Section: Introductionmentioning
confidence: 99%